Identifikasi Permasalahan Guru Menyusun RPP Pada Pembelajaran Online di SDN Gugus V Cakranegara Tahun Pelajaran 2020/2021 - Ni Putu Mega Widiani; I Ketut Widiada; Safruddin Safruddin (Journal of Science Instruction and Technology, 2021)
Education in Indonesia is currently undergoing significant changes, due to a new outbreak known as Covid19. In response to this phenomenon, the government immediately took a policy as outlined in the Circular Letter of the Minister of Education and Culture Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Corona Virus Disease (Covid-19) to regulate the teaching and learning process from home. The government's sudden decision and no preparation for the online learning process made some teachers experience difficulties. Teachers are required to be able to design simple learning according to current conditions. This study aims to measure the intensity of the problems faced by teachers in preparing lesson plans in the online learning process at SDN Gugus V Cakranegara in the 2020/2021 school year so that they can find out what problems are the highest faced by teachers based on the components of preparing the lesson plans. The approach used in this study is a quantitative descriptive approach. Data collection techniques using questionnaires, interviews, and documentation. Data analysis used the percentage formula. The results showed that the intensity of the problems faced by teachers in preparing lesson plans in the online learning process at SDN Gugus V Cakranegara in the 2020/2021 academic year was included in the medium category as many as 4 teachers (66.7%) and the highest problem faced by teachers was when compiling learning objectives with the number of teachers' frequency get the highest category, as many as 3 teachers (50%) get the high category and as many as 3 teachers (50%) get the medium category.